2019
DOI: 10.5539/enrr.v9n3p86
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Flora of Small-Scale Mined and Unmined-Sites in Dunkwa-East Municipality, Ghana

Abstract: The impacts of small-scale mining on the vegetal cover as well the livelihoods of communities in mined areas in developing countries such as Ghana are far-reaching. This study assessed the impacts of small-scale mining on flora of conservation and economic significance through quantification of species richness, and species diversity. Mined and unmined sites were chosen in the Dunkwa East Municipality of Ghana. Five belt transects each (200m × 200m) were constructed in both sites. Each belt transect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The dominance of Chromolena odorata was expected for the disturbed sites because Chromolena odorata is known to colonise disturbed areas due to their ready availability of seeds and their dispersal mechanisms ( Khare et al., 2018 ; Mandal and Joshi, 2014 ; Zachariades et al., 2009 ). In a similar study, Essandoh et al. (2019) revealed that the colonisation of Chromolena odorata accounted for 54% of the species composition in abandoned ASM sites in Ghana.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…The dominance of Chromolena odorata was expected for the disturbed sites because Chromolena odorata is known to colonise disturbed areas due to their ready availability of seeds and their dispersal mechanisms ( Khare et al., 2018 ; Mandal and Joshi, 2014 ; Zachariades et al., 2009 ). In a similar study, Essandoh et al. (2019) revealed that the colonisation of Chromolena odorata accounted for 54% of the species composition in abandoned ASM sites in Ghana.…”
Section: Discussionmentioning
confidence: 85%
“…These methods have differentiated impacts on the environment and are predominantly characterised by unfilled pits, landscape disturbance, and destruction of plant cover and community structure ( Mantey et al., 2017 ; Edwards et al., 2014 ). Each of these methods relates vegetation removal with cascading effects on the environment ( Essandoh et al., 2019 ; Bansah et al., 2016 ; Edwards et al., 2014 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations